Global warning and environmental laws - "Jadhav, H. V." (Mumbai, 2007)
Tsunamis and changing global climate have given us enough warnings to clean up our environment of its pollutants. Along with Education and Management ,the Environment Protection Laws are required to be strictly implemented to create a healthy surrounding. In this book title "GLOBAL WARNING AND ENVIRONMENT PROTECTION LAWS " important legislation son the subject are discussed. WATER ACT 1974,AIR ACT 1981,ENVIRONMENT PROTECTION ACT 1986,FACTORIES ACT 1948, WILD LIFE PROTECTION ACT 1972, PUBLIC LIABILITY INSURANCE ACT 1991,BIO-DIVERSITY .ACT 2002 ,LAWS OF INTERNATIONAL CONVENTIONS AND ENVIRONMENTAL COURTS. The book describes salient features of the acts ,environmental case studies ,public interest litigation ,citizen suits, useful terminologies and tables of standards for the day to day requirement of industries. The chapter are self explanatory and the language easy to follow.
Keywords: Environmental law